Apresiasi Estetika Dan Etnis Multikultur Di Indonesia: Mencegah Disharmoni, Menjaga Kebertahanan Nkri - Ketut Sumadi (Institut Seni Indonesia Denpasar, 2007)
The goal of this article is to reinforce the existence of the Republic of Indonesia (NKRI), by promoting a multicultural awareness and essential understanding of national diversity or heterogeneity. Every sort of culture and the living method stand in the same level. Therefore, there is no more cultural superiority and cultural inferiority. Attempt to appreciate every single ethnic art throughout the country must be a priority in keeping the existence of the ethnicity and appreciating the local culture. However, this racial protection must not create exclusive attitude that trivializes or undermines other tribal culture. Every single tradition or tribal culture in Indonesia has its own distinctive meaning and relevant value that contribute toward solving problems of the local people.